Precision of 655 nm Confocal Laser Profilometry for 3D surface texture characterisation of natural human enamel undergoing dietary acid mediated erosive wear. Issue 3 (March 2018) - Mullan, F.; Mylonas, P.; Parkinson, C.; Bartlett, D.; Austin, R.S.
Highlights: The precision of 3D surface texture measurement was superior for polished enamel in comparison to natural enamel. Polished enamel roughness increased whereas unpolished enamel toughness decreased after erosion. Future studies should investigate the response of natural enamel to erosion. Abstract: Objectives: To assess the precision of optical profilometry for characterising the 3D surface roughness of natural and polished human enamel in order to reliably quantify acid mediated surface roughness changes in human enamel. Methods: Forty-two enamel samples were prepared from extracted human molars and either polished flat or left unmodified. To investigate precision, the variability of thirty repeated measurements of five areas of one polished and one natural enamel sample was assessed using 655 nm Confocal Laser Profilometry. Remaining samples were subjected to forty-five minutes orange juice erosion and microstructural changes were analysed using Sa roughness change (μm) and qualitatively using surface/subsurface confocal microscopy. Results: Enamel surface profilometry from the selected areas revealed maximal precision of 5 nm for polished enamel and 23 nm for natural enamel. After erosion, the polished enamel revealed a 48% increase in mean (SD) Sa roughness of 0.10 (0.07) μm (P < 0.05), whereas in contrast the natural enamel revealed a 45% decrease in mean (SD) roughness of −0.32 (0.42) μm (P < 0.05). These data were supported by qualitative confocal images of the surface/subsurface enamel. Significance: This study demonstrates a method for precise surface texture measurement of natural human enamel. Measurement precision was superior for polished flat enamel in contrast to natural enamel however, natural enamel responds very differently to polished enamel when exposed to erosion challenges. Therefore, thus future studies characterising enamel surface changes following erosion on natural enamel may provide more clinically relevant responses in comparison to polished enamel.